2013
DOI: 10.1128/iai.00540-13
|View full text |Cite
|
Sign up to set email alerts
|

Functional Features of TonB Energy Transduction Systems of Acinetobacter baumannii

Abstract: Acinetobacter baumannii is an opportunistic pathogen that causes severe nosocomial infections. Strain ATCC 19606 T utilizes the siderophore acinetobactin to acquire iron under iron-limiting conditions encountered in the host. Accordingly, the genome of this strain has three tonB genes encoding proteins for energy transduction functions needed for the active transport of nutrients, including iron, through the outer membrane. Phylogenetic analysis indicates that these tonB genes, which are present in the genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 59 publications
(90 reference statements)
4
80
0
Order By: Relevance
“…A similar growth impairment under iron deficiency was reported by Zimbler et al for tonB1 and tonB2 deletion mutants of strain ATCC 19606 (42). Since the authors of the study could not generate a tonB3 deletion mutant by homologous recombination, the growth phenotype could not be assessed, and the authors concluded the TonB3-ExbB3-ExbD3 system was essential in A. baumannii.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…A similar growth impairment under iron deficiency was reported by Zimbler et al for tonB1 and tonB2 deletion mutants of strain ATCC 19606 (42). Since the authors of the study could not generate a tonB3 deletion mutant by homologous recombination, the growth phenotype could not be assessed, and the authors concluded the TonB3-ExbB3-ExbD3 system was essential in A. baumannii.…”
Section: Discussionmentioning
confidence: 67%
“…Interestingly, the tonB3 gene, but not the tonB1 and tonB2 genes (see Fig. S2 in the supplemental material), has recently been shown to be induced under iron-limiting conditions (42). The TonB3-ExbB3-ExbD3 system could therefore be a likely candidate for providing energy to PiuA and PirA siderophore receptors in A. baumannii.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, we identified a TonB system that is also Zur regulated. This could reflect a specialized system in A. baumannii, an organism that encodes several predicted TonB systems (53,54). Furthermore, other regulators, transporters, virulence factors, and secreted proteins have been identified as being Zur or Zn regulated in various bacterial species (39-45, 48, 50).…”
Section: Discussionmentioning
confidence: 99%